Aesthetics and modernity : essays - Heller, Agnes (Lexington Books, 2011)
Aesthetics and Modernity brings together Agnes Heller's most recent essays around the topics of aesthetic genres such as painting, music, literature and comedy, aesthetic reception, and embodiment. The essays draw on Heller's deep appreciation of aesthetics in all its forms from the classical to the Renaissance and the contemporary periods. Heller's recent work on aesthetics explores the complex and fraught status of artworks within the context of the history of modernity. For Heller, not only doesthe relation between aesthetics and modernity have to be looked at anew, but also the way in whic.